Monitoring dan Mitigasi Gas H2s Limbah Organik Tambak Intensif dengan Menggunakan Biomarker Sederhana - Arnold Kabangnga; Zulkhairiyah Zulkhairiyah; Chaterine Rumambo T.T (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
Monitoring and mitigation of organic waste materials is important to do for aquatic environment sustainability. This research aims to analyze hydrogen sulphide gases (H2S) contained in waste water and the index of scallop conditions as biomarkers.This research is conducted using the method of factorial design of 10 green shells that are approximately 6 cm in length is inserted into the aquarium containing 5 liters of sea water that has been contamination with organic waste sourced From supra intensive ponds in accordance with the concentration of treatment series ie; 50%, 35%, 15% and 0 (control) Waste Orgnik.Exposure is made for 96 hours. For the purposes of data index of the condition conducted a measurement of shellfish morfometry and drying shells with a temperature of 800C for 24 hours. The results showed that there were significant differences (p < 0.05) of hydrogen sulphide decline in water-media exposure to shells as well as differences in shell condition indexes based on the treatment concentration series.